Acquisition-dependent modulation of hippocampal neural cell adhesion molecules by associative motor learning - Navarro-López, Juan D.; Contreras, Ana; Touyarot, Katia; Herrero, Ana I.; Venero, César; Cambon, Karine; Gruart, Agnés; Delgado-García, José M.; Sandi, Carmen; Jiménez-Díaz, Lydia (Frontiers in Neuroanatomy, 2022)
It is widely accepted that some types of learning involve structural and functional changes of hippocampal synapses. Cell adhesion molecules NCAM, its polysialylated form PSA-NCAM, and L1 are prominent modulators of those changes. On the other hand, trace eyeblink conditioning, an associative motor learning task, requires the active participation of hippocampal circuits. However, the involvement of NCAM, PSA-NCAM and L1 in this type of learning is not fully known. Here, we aimed to investigate the possible time sequence modifications of such neural cell adhesion molecules in the hippocampus during the acquisition of a trace eyeblink conditioning. To do so, the hippocampal expression of NCAM, PSA-NCAM and L1 was assessed at three different time points during conditioning: after one (initial acquisition), three (partial acquisition) and six (complete acquisition) sessions of the conditioning paradigm. The conditioned stimulus (CS) was a weak electrical pulse separated by a 250-ms time interval from the unconditioned stimuli (US, a strong electrical pulse). An acquisition-dependent regulation of these adhesion molecules was found in the hippocampus. During the initial acquisition of the conditioning eyeblink paradigm (12 h after one and three days of training), synaptic expression of L1 and PSA-NCAM was transiently increased in the contralateral hippocampus to the paired CS US presentations, whereas, when the associative learning was completed, such increase disappeared, but a marked and bilateral up-regulation of NCAM was found. In conclusion, our findings show a specific temporal pattern of hippocampal CAMs expression during the acquisition process, highlighting the relevance of NCAM, PSA-NCAM, and L1 as learning modulated molecules critically involved in remodeling processes underlying associative motor-memories formation.